The Origins of Contemporary France, Complete Table of Contents - Taine, Hippolyte, 1828-1893; Rom, Svend; Widger, David, 1932-2021?; Durand, John, 1822-1908 (Salt Lake City, UT : Project Gutenberg, 2008)
"The Origins of Contemporary France, Complete Table of Contents" by Hippolyte Taine is a historical account written during the late 19th century. This comprehensive work seeks to explore the sociopolitical developments and philosophical shifts that have shaped modern France, particularly in relation to the ancient regime, the French Revolution, and the rise of Napoleon Bonaparte. Taine's exploration encompasses a detailed analysis of the structures, morals, and doctrines inherent to these pivotal historical moments. In the first volume, Taine focuses on the impact of the ancient regime, outlining the privileges and roles of the clergy, nobility, and monarchy, and the resulting societal dynamics. He portrays the transition into the French Revolution, illustrating how the ancien régime's failures led to widespread disenfranchisement and discontent among the populace. As the narrative progresses into discussions of the revolutionary fervor, Taine examines the emergence of political factions like the Jacobins, the eventual escalation into terror, and the centralization of power under Napoleon. Through an intricate tapestry of historical events and philosophical ideas, Taine captures the evolution of France against the backdrop of crises and reforms that heralded its modern identity. (This is an automatically generated summary.)
Release date is 2008-06-22
David Widger
Keywords: France -- History -- Revolution, 1789-1799; Indexes